Transferrin Types and Their Correlation with Some Important Metabolites in the Serum of Indian Sheep - Adhikari, Alka; Mehta, S.P.S. (Asian Journal of Chemistry, 2016)
Seven transferrin phenotypes, viz., Tf-AA, Tf-BB, Tf-AB, Tf-AC, Tf-BC, Tf-CC and Tf-ME were observed in the serum of Indian shtep. The average concentrations of some important metabolites were correlated with the transferrin types.